Need and Proposal of Way of Transformation of Classical Into Digital Bank with Support of Information and Mobile Technologies - Sajić, Mirko; Bundalo, Zlatko; Bundalo, Dušanka (The European Journal of Applied Economics, 2019)
In the paper is considered and described the need that practically and effectively be implement the transformation of a standard classical bank into a digital bank, and is proposed a way of transformation using information and mobile technologies. The paper has the aim to provide clear evidences about the necessity of transformation banks from the present classical form into a new form of organizing and providing of services, into so-called digital bank. At that the great influence of the mobile digital information technologies on the entire financial sector is also emphasized. The problems that appeared because of a divergence of the existing concept of the bank development and the way on what a modern client wants to obtain the service, according to the possibilities of modern mobile digital technologies, are clearly explained. Together with the reasons that require changes, proposals how to practically perform these changes are also given. The basic principles of transition of the bank from a classical to a digital form, through the so-called hybrid transformation period, are presented and proposed are some concrete solutions.